Political risk and foreign direct investment in Nigeria: new empirical evidence - Koko, Musa Hatim; Yatiban, Aminurraasyid; Zengeni, Knocks Tapiwa (Growing Science Ltd., 2017)
The positive effect of globalization has continued to impact FDI inflow to developing countries during the last decade except for the rising influence of political risk in host locations. Mixed outcomes have trailed the findings related to the studies on FDI and political risk relationship and in particular on African countries like Nigeria.This paper investigated the effect of political risk on FDI inflow to Nigeria using secondary data from 2000 to 2014 using simple linear regression. The study combined from select variables, the institutional factors with location determinants peculiar to Nigeria’s risk environment. It is found that political risk holds a positive and significant association with FDI to Nigeria but not close enough to inhibit the inflow of foreign investment to the country.However, the findings provide a strong basis for policy shift in relation to security, country promotion and rebranding as well strengthening of institutions.